STAT4, TRAF3IP2, IL10, and HCP5 Polymorphisms in Sjögren's Syndrome: Association with Disease Susceptibility and Clinical Aspects. (10th February 2019) - Colafrancesco, Serena; Ciccacci, Cinzia; Priori, Roberta; Latini, Andrea; Picarelli, Giovanna; Arienzo, Francesca; Novelli, Giuseppe; Valesini, Guido; Perricone, Carlo; Borgiani, Paola
Abstract : Sjögren's syndrome (SS) is a chronic autoimmune condition characterized by autoantibody production, sicca syndrome, and periepithelial lymphocytic lesions in target tissues. A predisposing genetic background is likely, and, to date, several polymorphisms in non-HLA genes have been explored with interesting results. We investigated the association between the STAT4, TRAF3IP2, HCP5, and IL10 polymorphisms and SS susceptibility and their possible role in the modulation of clinical and laboratory features. 195 consecutive patients with SS were enrolled and clinical and laboratory data were collected. 248 age- and sex-matched healthy subjects were used as controls. Genotyping was performed by allelic discrimination assays. A case-control association study and a phenotype-genotype correlation analysis were performed. A genetic risk profile was developed considering the risk alleles. Both the variant alleles of rs7574865 in the STAT4 gene and rs3099844 in the HCP5 gene were significantly more prevalent in patients than in controls (OR = 1.91 andOR = 2.44, respectively). The variant allele of rs3024505 of IL10 resulted to be a susceptibility allele (OR = 1.52 ), while the variant allele of rs1800872 seemed to confer a protective effect for the development of the disease (OR = 0.65 ). A risk genetic profile showed a higher probability to develop the disease in subjects with at least three risk alleles; subjects with 4 risk alleles were not observed in the controls. HCP5 rs3099844 was associated with anti-SSA (P = 0.006, OR = 3.07 ) and anti-SSB (P = 0.005, OR = 2.66 ) antibodies, severity of focus score (P = 0.03, OR = 12 ), and lymphoma development (P = 0.002, OR = 7.23 ). Patients carrying the STAT4 rs7574965 variant allele had a higher risk of monoclonal component and leukopenia (P = 0.002, OR = 7.6 ;P = 0.048, OR = 2.01, respectively). We confirmed the association of SS with the STAT4 and IL10 genes and we describe a novel association with HCP5 . In particular, we describe an association of this specific SNP of HCP5 not only with disease development but also with autoantibody production and focus score suggesting a potential contribution of this variant to a more severe phenotype.